PERANCANGAN DAN PEMBUATAN SISTEM KOMPETISI SEPAK BOLA BERBASIS WEB - Yudho Yudhanto; Andesta Putra (IJAI (Indonesian Journal of Applied Informatics), 2017)
Football is one of the most famous sport in the world. In Indonesia, this sport has become a favored game that people of all ages. However, from the various tournaments that have been held, there are some drawbacks one of which is the lack of statistical data regarding the schedule and complete pertadingan that can be known quickly by football fans, football observers, club officials and players themselves. Therefore, the need for a system to simplify the process of delivering all the information about the competition of football going to the actors of football.Implementation of the creation of a system of web-based football competition using PHP and MySQL that can provide information on the match statistics from the competition is complete and can be accessed quickly by the actors of football.